Emerging Therapies in the Management of Advanced-Stage Gastric Cancer - Kumar, Vivek; Soni, Parita; Garg, Mohit; Kamholz, Stephan; Chandra, Abhinav B. (Frontiers in Pharmacology, 2018)
Globally, gastric malignancy contributes to significant cancer-related morbidity and mortality. Despite the recent approval of two targeted agents (i.e. trastuzumab and ramucirumab), treatment options for advanced-stage gastric cancer are limited and overall clinical outcomes for patients with advanced-stage gastric cancer remain poor. Numerous agents that are active against novel targets have been evaluated in randomized trials; however, most have produced disappointing results owing to the molecular heterogeneity of gastric cancer. The Cancer Genome Atlas (TCGA) project recently proposed a new classification system for gastric cancer that includes four different tumor subtypes based on molecular characteristics. This change led to the identification of several distinct and potentially targetable pathways. However, most agents targeting these pathways did not elicit any meaningful clinical benefit when used for the treatment of advanced-stage gastric cancer. Most advanced-stage gastric cancer trials currently focus on agents that modulate tumor microenvironments and cancer cell stemness. In this review, we summarize data regarding novel compounds that have shown efficacy in early phase studies and show promise as effective therapeutic agents, with special emphasis on those for which phase III trials are either planned or underway.